PERTANGGUNGJAWABAN PENYIDIK YANG MELAKUKAN MALADMINISTRASI - Aji Frastya Irawan (Fakultas Hukum Universitas Islam Malang, 2021)
ABSTRACTMaladministration that often occurs in various government agencies shows that the law and supervision in Indonesia against maladministration is still very lacking. Looking at Law Number 37 of 2008 concerning Maladministration in article 1 Maladministration is an act against the law, goes beyond authority, uses authority for other purposes, including negligence or neglect of legal obligations in the administration of public services carried out by state administrators and governments that cause material losses as well as immaterial for the public and individuals, therefore the Ombudsman is a state institution that has the authority to supervise the implementation of public services, both those organized by the government and state administrators, including State Owned Enterprises, Regional Owned Enterprises and State Owned Legal Entities as well as private or individual.Keywords: Maladministration, Ombudsman, InvestigatorABSTRAKMaladministrasi yang sering terjadi di berbagai badan pemerintahan menunjukkan hukum dan pengawasan di Indonesia terhadap Maladministrasi masih sangat kurang tegas. Melihat pada Undang-Undang Nomor 37 tahun 2008 tentang Maladministrasi dalam pasal 1 Maladministrasi adalah perbuatan melawan hukum, melampaui wewenang, menggunakan wewenang untuk tujuan lain, termasuk kelalaian atau pengabaian kewajiban hukum dalam penyelenggaraan pelayanan publik yang dilakukan oleh penyelenggara negara dan pemerintahan yang menimbulkan kerugian materil maupun immateriil bagi masyarakat dan orang perseorangan oleh karenanya Ombudsman adalah lembaga negara yang mempunyai kewenangan mengawasi penyelenggaraan pelayanan publik baik yang diselenggarakan pemerintah maupun penyelenggara negara termasuk Badan Usaha Milik Negara, Badan Usaha Milik Daerah, dan Badan Hukum Milik Negara serta badan swasta.Kata Kunci : Maladministrasi, Ombudsman, Penyidik